Forecasting the Brazilian Real and the Mexican Peso: Asymmetric Loss, Forecast Rationality, and Forecaster Herding - Ulrich Fritsche; Christian Pierdzioch; Jan-Christoph Ruelke; Georg Stadtmann (Hamburg University, Department Socioeconomics, 2012)
Using forecasts of the Brazilian real and the Mexican peso, we analyze the shape of the loss function of exchange-rate forecasters and the rationality of their forecasts. We find a substantial degree of cross-sectional heterogeneity with respect to the shape of the loss function. While some forecasters seem to forecasts under an asymmetric loss function, symmetry of the loss function cannot be rejected for other forecasters. An asymmetric loss function does not necessarily make survey data of exchange-rate forecasts look rational, and the loss function seems to depend not only on the forecast error.
Keywords: F31; D84; 330; Exchange rate; Forecasting; Loss function